2020
DOI: 10.1017/s027226311900072x
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Emotional and Foreign Language Context in Content Learning

Abstract: Prior research has found reduced emotionality with foreign language use, especially with single words, but what happens if emotionality is conveyed throughout a longer text? Does emotionality affect how well we remember and associate information, that is, content learning? We played participants descriptions of two invented countries and tested how well they remembered facts about these countries. Each participant listened to one positive and one neutral description, which was read either in their native langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
3
6
0
Order By: Relevance
“…This support comes from the influence of valence and arousal demonstrated in the mixed-effects modeling analyses and qualitative findings regarding reading topics and target vocabulary items. In response to the first research question, the results of the vocabulary tests across the three emotion-laden reading contexts in the current study generally support the findings that both emotional valence (Frances et al, 2020b; Kensinger, 2009; Mizrak & Öztekin, 2016) and emotional arousal (Frances et al, 2020a; Kensinger, 2009) influence learning and retention outcomes. Specifically, a mixed-effects analysis did return significant results, predicting the neutral and negative readings as the best contexts for vocabulary learning for both FLLs and HLLs.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This support comes from the influence of valence and arousal demonstrated in the mixed-effects modeling analyses and qualitative findings regarding reading topics and target vocabulary items. In response to the first research question, the results of the vocabulary tests across the three emotion-laden reading contexts in the current study generally support the findings that both emotional valence (Frances et al, 2020b; Kensinger, 2009; Mizrak & Öztekin, 2016) and emotional arousal (Frances et al, 2020a; Kensinger, 2009) influence learning and retention outcomes. Specifically, a mixed-effects analysis did return significant results, predicting the neutral and negative readings as the best contexts for vocabulary learning for both FLLs and HLLs.…”
Section: Discussionsupporting
confidence: 81%
“…Given the present findings that the topics perceived as qualitatively negative, at least in part, predict better vocabulary learning outcomes, it is important to note that the literature on positive psychology and positive emotion within SLA (e.g., Frances et al, 2020aFrances et al, , 2020bFredrickson, 2003;Fredrickson & Branigan, 2005;MacIntyre & Gregersen, 2012b;MacIntyre et al, 2016) emphasizes the advantages of positive emotions and contexts over negative emotions for language achievement. However, studies also exist within psychology noting in some cases the detriment of negative emotional content on memory (e.g., Bisby et al, 2018) and in others the benefits of negative stimuli on recall (Hinojosa et al, 2020;Mizrek and Öztekin, 2016).…”
Section: The Association Between Emotion-laden Texts and Vocabulary Learningmentioning
confidence: 83%
See 1 more Smart Citation
“…Although against our initial hypothesis, this suggests that access to contextual information is enough to maintain the positive influence of diversity on word learning, despite the obvious difficulty of processing information in a non-native language. A prior study from the same authors found similar results with emotionality, where the effects of this variable were independent of language 49 . This supports the idea that the strategies for improving learning in the native language can apply to the foreign language, suggesting also that learning new vocabulary in one's native and foreign languages engage similar mechanisms.…”
Section: Discussionsupporting
confidence: 67%
“…Frances et al [30] took a similar approach to the one in the present study, where participants learn new information-in their case new content, instead of new vocabulary-that was embedded in a positive or a neutral semantic context. This contrasts with prior studies that focused either on memory for known words or on the acquisition of new lexical items for known concepts.…”
Section: Introductionmentioning
confidence: 99%